Lab practices that improve coronavirus disease 2019 detection accuracy using real-time PCR. Issue 3 (10th September 2022) - Soufan, Ghadir; Berro, Nour; Nahle, Sahar; Darwish, Malak; Ghaddar, Maysaa; Makki, Mohamad; Younes, Mahmoud; Sater, Fadi Abdel
Abstract : ABSTRACT: The number of coronavirus disease 2019 (COVID-19) cases significantly increased with the emergence of multiple variants of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). This has led to an ongoing effort focused on developing the diagnostic detection tests. Among the currently available tests, real-time reverse transcriptase PCR (RT-PCR) has been considered as the 'golden method' for the detection of SARS-COV-2. However, a significant number of inaccurate (false-negative/false-positive) results have been reported in spite of this method's reliability and effectiveness. These unreliable results may arise because of various issues encountered throughout the entire testing process starting with the sampling phase, going through the PCR process, and ending with the result analysis. This article aims to shed light on the errors that occur during the COVID-19 testing process and suggest ways to overcome them effectively. Accurate testing could be optimized by following the correct swabbing technique, using adequate RT-PCR kits and controls, setting clear lab guidelines, and properly interpreting the results.